Potential Candidates for Focal Therapy in Prostate Cancer in the Era of Magnetic Resonance Imaging–targeted Biopsy: A Large Multicenter Cohort Study - von Hardenberg, Jost; Borkowetz, Angelika; Siegel, Fabian; Kornienko, Kira; Westhoff, Niklas; Jordan, Tobias B.; Hoffmann, Manuela; Drerup, Martin; Lieb, Verena; Taymoorian, Kasra; Schostak, Martin; Ganzer, Roman; et al. (European Urology Focus, 2020)
Background: Focal therapy (FT) with its favorable side-effect profile represents an option between active surveillance and traditional whole-gland treatment in localized prostate cancer (PCa). Consensus statements recommend eligibility criteria based on magnetic resonance imaging (MRI)-targeted and systematic combination biopsy. Objective: To estimate the future potential of FT by analyzing the number of men eligible for FT among all men with biopsy-proven PCa and to judge the potential of different energy sources. Design, setting, and participants: Consensus criteria on FT were analyzed. Patients with biopsy-proven PCa from six tertiary referral hospitals and one outpatient practice in Germany had received a software-based combination biopsy. Men with Prostate Imaging Reporting and Data System (PI-RADS) ≥3 lesions based on PI-RADS v2 were included. Outcome measurements and statistical analysis: Patients were analyzed for potential treatment by FT and hemiablation. MRI lesions were mapped according to prostatic zones. Results and limitations: In total, 2371 patients were analyzed. According to consensus criteria (biopsy-proven unifocal lesion of International Society of Urological Pathology [ISUP] grade group ≤2, prostate-specific antigen [PSA] ≤15 ng/mL, and life expectancy >10 yr), 303 patients (12.8%; ISUP 1: n = 148 [6.2%]; ISUP 2: n = 155 [6.5%]) were potential candidates for FT. A maximum PSA level of <10 ng/mL would exclude further 60 (2.5%) of these men. The eligibility for hemiablation is slightly higher (16.2%). Unifocal lesions (n = 288) were equally distributed within the prostate (anteriorly [31%], apically [29%], and dorsally [36%]). Conclusions: With adherence to consensus statements, only a minority of PCa patients present as potential candidates for FT. Distribution of tumor localization suggests the need for different energy modalities to warrant an optimal FT treatment. Patient summary: We analyzed how many men who receive a magnetic resonance imaging–targeted and systematic prostate biopsy are candidates for the experimental focal therapy of the prostate. When following expert recommendations, only a small number of men are potential candidates for this alternative treatment. This study shows that less than one out of seven men is an eligible candidate for focal ablation after combined magnetic resonance imaging–targeted and systematic biopsy. Eligibility for focal therapy was defined as unifocal prostate cancer of International Society of Urological Pathology grade group ≤2 and prostate-specific antigen <15 ng/mL. The potential for hemiablation is slightly higher, with one out of six men being eligible for focal ablation. Modality-specific limitations are not incorporated.
CRIS-Team Scopus Importer:2020-11-06
Keywords: Biopsy; Consensus; Eligibility criteria; Focal therapy; Focal therapy modalities; Hemiablation; Multiparametric magnetic resonance imaging; Partial gland ablation; Patient selection; Prostate neoplasms